Abnormal psychology - "Sarason, Irwin G" (Delhi, 2004)
As in previous editions, one of our major goals is to introduce students of abnormal psychology to (1) the nature of psychopathology, (2) how clinicians diagnose and treat it, and (3) the research that contributes to understanding maladaptive behaviour, its prevention and treatment. Another goal is to explain the growing complexity of psychopathology in a clear and engaging way. Complexity does not have to be confusing. With a few organizing principles, it can lead to an appreciation of richness. This is exactly what occurs in a fine Persian carpet that may have several complex designs integrated by means of a few organizing esthetic principles. In this edition, we have made a social effort to introduce the student to complexity so that it becomes rich and nuanced rather than just potently confusing information.
Keywords: Psychology